The Levels of Critical and Creative Thinking among Palestinian University Students in the West Bank, Palestine - Khalili, Fakher Nabeel Mohamad; Sleem, Heba Khaled Ahmad; Sayegh, Ashraf Munther Ahmad (Dirasat: Educational Sciences, 2022)
Objectives: The study aims to investigate levels of critical and creative thinking among university students in the West Bank, Palestine. It also aims to test for any possible correlation between critical and creative thinking. Methods: A descriptive correlational research design was used and a sample of 414 students was selected. The California critical thinking skills and the cognitive processes associated with creativity test were utilized. Results: The results show that the level of critical thinking among students was low, while the level of creative thinking was moderate. The correlation coefficient was statistically significant in the positive direction (r = 0.687). The results show that students of humanities are more creative than students of scientific disciplines. Students with high GPAs and those with advanced academic years are more critical thinkers compared to the others. Male students were better than female students in critical thinking. Conclusions: The study recommends that thinking styles should be included in educational activities at universities.